Expanding the Market through Digitalization: Identification Tool for MSME’s to Their Potential Costumer - Hafianti, Silvi; Widiastuti, Nur; Apriani , Triana (Journal Corner of Education, Linguistics, and Literature, 2024)
This research aims to provide simple tools for MSMEs to understand the market conditions they are facing. Moreover, this research also intended to provide information for MSMEs on where customers can buy their products and their ability to access the digital marketing platform they will use. The expected users of these tools are MSMEs. Hence, the important aspect of constructing the tools highlighted in this research is simple, general, and inexpensive. Three key questions try to answer in this research are (1) where the customers are; (2) whether there are potential customers for MSMEs; and (3) do they have the ability to access the digital marketing platform that the MSMEs will try to use in this pandemic. This research proposes two types of indicators for targeted digital marketing. The first indicator is the regional indicator, which shows the capacity of the regions to spend or consume. The second indicator is a household indicator that shows the purchasing ability to consume and the ability of a household to access a digital platform. The data is estimated at the provincial level using annual data obtained from Statistics Indonesia. The results show that the provinces in Java currently have the highest potential for accessing digital platforms. However, analyzing the data using the growth variables shows a big potential for provinces in Kalimantan and Sulawesi as the next destination for expanding the digital platform.